La Consentida : Settlement, Subsistence, and Social Organization in an Early Formative Mesoamerican Community - Hepp, Guy David (Book collections on Project MUSE., 2019)
"Exploring Early Formative- period transitions in residential mobility, subsistence, and social organization at La Consentida in coastal Oaxaca, Mexico. Demonstrating how La Consentida transformed during moments of socioeconomic change in the ancient Americas providing a new way of thinking about the social complexities of Mesoamerican communities"--Provided by publisher